2019
DOI: 10.1021/acs.jafc.9b04374
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Added l-Cysteine with 2-Threityl-thiazolidine-4-carboxylic Acid Derived from the Xylose–Cysteine System Affecting Its Maillard Browning

Abstract: The Maillard reaction under a stepwise increase of temperature using L-cysteine as the indicator was performed to determine the formation conditions for the preparation of 2-threityl-thiazolidine-4-carboxylic acid (TTCA) which was the main Maillard reaction intermediate (MRI) derived from the xylose (Xyl)−cysteine (Cys) model system in aqueous medium. To clarify the indicating mechanism of Cys for the TTCA formation, the thermal model systems of TTCA−Cys and TTCA solutions were investigated. The browning of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 38 publications
(75 reference statements)
4
38
0
Order By: Relevance
“…Synthesis and Purification Asp−Xyl-ARP. The aspartic acid− xylose ARP (Asp−Xyl-ARP) were prepared according to the method of Zhai et al 21 Xylose and aspartic acid were dissolved in 200 mL of deionized water (total concentration of 43 mg/mL) in a 2:1 M ratio. The conditions were scaled down based on industrial conditions, and ARP preparation would be scaled up proportionally for industrialization in the future.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Synthesis and Purification Asp−Xyl-ARP. The aspartic acid− xylose ARP (Asp−Xyl-ARP) were prepared according to the method of Zhai et al 21 Xylose and aspartic acid were dissolved in 200 mL of deionized water (total concentration of 43 mg/mL) in a 2:1 M ratio. The conditions were scaled down based on industrial conditions, and ARP preparation would be scaled up proportionally for industrialization in the future.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The solution was rapidly cooled in an ice bath for further purification. The purification procedure of TTCA was accomplished according to our previous study …”
Section: Methodsmentioning
confidence: 99%
“…The quantitative analysis of TTCA and ARP was performed by high-performance liquid chromatography–evaporative light scattering detection (HPLC-ELSD) using the purified compounds prepared in our laboratory as external standards, referring to our previous study . The analytical-grade Cys and Xyl were used as external standards for their quantitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that addition of cysteine to MR system can inhibit the brown color formation and lead to light‐colored Maillard flavor‐enhancing peptides (Eric et al., 2013). Another study revealed that these peptides are generated after the interaction of cysteine and amadori compound and inhibition of dicarbonyl compound (Zhai et al., 2019). A recent study reported the use of glucosamine, a highly reactive amino sugars for the generation of light‐colored Maillard flavor‐enhancing peptides (Fu et al., 2019).…”
Section: Biological Activity Of Mr Productsmentioning
confidence: 99%